2004
DOI: 10.1002/pola.20522
|View full text |Cite
|
Sign up to set email alerts
|

Chemical alteration of poly(tetrafluoroethylene) Teflon induced by exposure to vacuum ultraviolet radiation and comparison with exposure to hyperthermal atomic oxygen

Abstract: The chemical alteration of poly(tetrafluoroethylene) Teflon by vacuum ultraviolet radiation (VUV) (115-400 nm) has been examined with X-ray photoelectron spectroscopy (XPS). The initial F/C atom ratio of 1.98 decreases to 1.65 after a 2-h exposure. The F/C atom ratio is further reduced to a steady-state value of 1.60 after a 74-h exposure. The high-resolution XPS C1s data indicate that new chemical states of carbon form as F is removed and that the relative amounts of these states depend on the F content of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…[18,21]. C-F bond cleavage with formation of -CF 2 CF CF 2 -centers was also observed in XPS studies of VUV irradiated PTFE [9]. These latter authors also suggest the formation of carbocation centers due to loss of F À which would not be observed by EPR.…”
Section: Mechanism Of Polytetrafluoroethylene Radiolysismentioning
confidence: 60%
See 1 more Smart Citation
“…[18,21]. C-F bond cleavage with formation of -CF 2 CF CF 2 -centers was also observed in XPS studies of VUV irradiated PTFE [9]. These latter authors also suggest the formation of carbocation centers due to loss of F À which would not be observed by EPR.…”
Section: Mechanism Of Polytetrafluoroethylene Radiolysismentioning
confidence: 60%
“…Because of the technological importance of PTFE, there has been a substantial amount of work on its radiation [1][2][3][4][5][6][7][8] chemistry. Recent work has focused on the stability of PTFE under VUV irradiation for spacecraft applications [9]. In this work, PTFE was irradiated under vacuum conditions and the resulting polymer was studied by Xray photoelectron spectroscopy (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…353 Indeed, to improve the surface hydrophilicity of PVDF, many investigations have been devoted to the surface modification of fluoropolymers by chemical, 354 plasma, 355 irradiation, 356 corona discharge, 357 flame, 358 and vacuum ultraviolet radiation. 359 For example, the synthesis of PVDF-g-PMAAc (where MAAc stands for methacrylic acid) was reported in 1998 by Mascia and Hashim 360 according to a two-step procedure (Scheme 50). Furthermore, Liu et al 361 also used that strategy to synthesize PVDF-g-PEOMA graft copolymer, where PEO-MA stands for poly(ethylene glycol methacrylate).…”
Section: Conventional Radical Copolymerizationmentioning
confidence: 99%
“…However, biomedical devices can be easily contaminated, because of the low surface energy and hydrophobility of PVDF. To improve surface hydrophilicity of PVDF, a large amount of work has been devoted to the surface modification of fluoropolymers by chemical,11 plasma,12–14 irradiation,15 corona discharge,16 flame,17 ozone treatment,18 and vacuum ultraviolet radiation 19. It was demonstrated that through the intelligent choice of the molecular functionality and the spatial configuration of the graft chains, the molecules of a fluoropolymer surface can be redesigned to impart new and specific functionalities to the fluoropolymer surface.…”
Section: Introductionmentioning
confidence: 99%